Phenotypic spectrum and clinical course of single large-scale mitochondrial DNA deletion disease in the paediatric population: a multicentre study. Issue 1 (6th December 2021) - Björkman, Kristoffer; Vissing, John; Østergaard, Elsebet; Bindoff, Laurence A; de Coo, Irenaeus F M; Engvall, Martin; Hikmat, Omar; Isohanni, Pirjo; Kollberg, Gittan; Lindberg, Christopher; Majamaa, Kari; Naess, Karin; et al.
Abstract : Background: Large-scale mitochondrial DNA deletions (LMD) are a common genetic cause of mitochondrial disease and give rise to a wide range of clinical features. Lack of longitudinal data means the natural history remains unclear. This study was undertaken to describe the clinical spectrum in a large cohort of patients with paediatric disease onset. Methods: A retrospective multicentre study was performed in patients with clinical onset <16 years of age, diagnosed and followed in seven European mitochondrial disease centres. Results: A total of 80 patients were included. The average age at disease onset and at last examination was 10 and 31 years, respectively. The median time from disease onset to death was 11.5 years. Pearson syndrome was present in 21%, Kearns-Sayre syndrome spectrum disorder in 50% and progressive external ophthalmoplegia in 29% of patients. Haematological abnormalities were the hallmark of the disease in preschool children, while the most common presentations in older patients were ptosis and external ophthalmoplegia. Skeletal muscle involvement was found in 65% and exercise intolerance in 25% of the patients. Central nervous system involvement was frequent, with variable presence of ataxia (40%), cognitive involvement (36%) and stroke-like episodes (9%). Other common features were pigmentary retinopathy (46%), short stature (42%), hearing impairment (39%), cardiac disease (39%), diabetes mellitus (25%) and renal disease (19%). Conclusion: Our study provides new insights into the phenotypic spectrum of childhood-onset, LMD-associated syndromes. We found a wider spectrum of more prevalent multisystem involvement compared with previous studies, most likely related to a longer time of follow-up.